Importance of reservoir tributaries to spawning of migratory fish in the upper parana river - Silva, P. S. da; Makrakis, M. C.; Miranda, L. E.; Makrakis, S.; Assumpcao, L.; Paula, S.; Dias, J. H. P.; Marques, H. [UNESP] (Wiley-Blackwell, 2015)
Regulation of rivers by dams transforms previously lotic reaches above the dam into lentic ones and limits or prevents longitudinal connectivity, which impairs access to suitable habitats for the reproduction of many migratory fish species. Frequently, unregulated tributaries can provide important habitat heterogeneity to a regulated river and may mitigate the influence of impoundments on the mainstem river. We evaluated the importance of tributaries to spawning of migratory fish species over three spawning seasons, by comparing several abiotic conditions and larval fish distributions in four rivers that are tributaries to an impounded reach of the Upper Parana River, Brazil. Our study confirmed reproduction of at least 8 long-distance migrators, likely nine, out of a total of 19 occurring in the Upper Parana River. Total larval densities and percentage species composition differed among tributaries, but the differences were not consistent among spawning seasons and unexpectedly were not strongly related to annual differences in temperature and hydrology. We hypothesize that under present conditions, densities of larvae of migratory species may be better related to efficiency of fish passage facilities than to temperature and hydrology. Our study indicates that adult fish are finding suitable habitat for spawning in tributaries, fish eggs are developing into larvae, and larvae are finding suitable rearing space in lagoons adjacent to the tributaries. Our findings also suggest the need for establishment of protected areas in unregulated and lightly regulated tributaries to preserve essential spawning and nursery habitats. Copyright (c) 2014 John Wiley &Sons, Ltd.
Keywords: Spawning areas; Nursery habitats; Fish migration; Reproduction; Large river system